ISOLASI DAN PENENTUAN KONDISI KERJA OPTIMUM LIPASE DARI PERKECAMBAHAN BIJI DURIAN (Durio zibethinus L) - Dzulkarnain Dzulkarnain; Winni Astuti; Saibun Sitorus (PROSIDING SEMINAR KIMIA, 2018)
This research was conducted to isolate and to know the optimum lipase working conditions (pH, temperature and concentration of substrate), and to know lipase activity from germination of durian seed (Durio zibethinus L.). Isolation is done by 2 stages namely, homogenization and centrifugation. Centrifugation is done at a speed of 12000 rpm with a temperature of 4°C for 30 minutes. Activity by using titration method and protein concentration using method. The optimum lipase temperature obtained was 60°C, optimum pH was 7, and the optimum substrat concentration was 1 % v/v. The lipase specific activity yielded 0,221 U/mg. Keywords: lipase, Durio zibethinus L., Lipase specific activity.